The career advancement experience of gay Mexican American men in corporate America - Franco, Andres (My University, 2025)
The Latino population embodies a rich tapestry of customs, cultures, and histories, yet those who navigate both Latino and LGBTQ+ identities, particularly gay Mexican American Men remain underrepresented in white collar professional roles and are often overlooked in research and organizational policy design. Existing scholarship tends to isolate race or sexual orientation, overlooking how their intersection compounds barriers to career development, advancement, and inclusion. Guided by intersectionality and social identity theory, and enhanced by a testimonio methodology, this narrative inquiry explores how gay Mexican American men interpret and navigate opportunities for career advancement in corporate America. By collecting and analyzing personal narratives, the study examines how intersecting identities shape professional trajectories, resilience strategies, and perceptions of opportunity and exclusion, offering valuable insights for scholars, practitioners, and policymakers committed to fostering equitable and inclusive workplaces.
Keywords: Mexican American; Gay Mexican American men; Corporate America; Career advancement; Intersectionality; Narrative inquiry